Layer-defect toughened hierarchically structured diamond composites. (17th February 2023) - Ma, Xiaoliang; Shi, Liping; Yang, Lin; Yi, Jian; Wang, Bo; Li, Mingwei; Zheng, Bing; Hou, Chengyu; Ye, Lin; Zhong, Yesheng; He, Xiaodong
Highlights: A new diamond toughening mechanism was demonstrated that inhibits crack propagation and reduces crack tip stress intensity by introducing layer-defects. Twin boundaries and phase boundaries have limited effect on toughening of the diamond composite. The fracture toughness of diamond with layer-defects can be up to 5.6 times that of defect-free diamond. Abstract: Recently synthesized diamond composites containing interfaced polytypes, nanograins, and nanotwins show exceptional fracture toughness. Layer defects with enlarged interlayer distances and substantial sp 2 bonding are commonly observed in such diamond composites. By using molecular dynamics simulations, we demonstrate that twin boundaries and phase boundaries have limited effect on toughening of the diamond composite. A diamond toughening mechanism that inhibits crack propagation and reduces crack tip stress intensity by introducing layer defects is demonstrated. Stress concentration around the crack tip can cleave nonpenetrating layer defects into partially deflected cracks, which dissipate fracture energy and stress concentration over a larger space region compared with a defect-free model, increasing fracture toughness. The toughening mechanism offers fundamental insight into understanding the fracture toughness of hierarchically structured diamond and is verified via comparison to previously published experimental results. The tradeoff between hardness and toughness in diamond composites may eventually be overcome by introducing these uniformly distributed layer defects.